Covalent labeling and mass spectrometry reveal subtle higher order structural changes for antibody therapeutics. Issue 3 (3rd April 2019) - Limpikirati, Patanachai; Hale, John E.; Hazelbaker, Mark; Huang, Yongbo; Jia, Zhiguang; Yazdani, Mahdieh; Graban, Eric M.; Vaughan, Robert C.; Vachet, Richard W.
ABSTRACT: Monoclonal antibodies are among the fastest growing therapeutics in the pharmaceutical industry. Detecting higher-order structure changes of antibodies upon storage or mishandling, however, is a challenging problem. In this study, we describe the use of diethylpyrocarbonate (DEPC)-based covalent labeling (CL) – mass spectrometry (MS) to detect conformational changes caused by heat stress, using rituximab as a model system. The structural resolution obtained from DEPC CL-MS is high enough to probe subtle conformation changes that are not detectable by common biophysical techniques. Results demonstrate that DEPC CL-MS can detect and identify sites of conformational changes at the temperatures below the antibody melting temperature (e.g., 55 ᴼC). The observed labeling changes at lower temperatures are validated by activity assays that indicate changes in the Fab region. At higher temperatures (e.g., 65 ᴼC), conformational changes and aggregation sites are identified from changes in CL levels, and these results are confirmed by complementary biophysical and activity measurements. Given the sensitivity and simplicity of DEPC CL-MS, this method should be amenable to the structural investigations of other antibody therapeutics.